2017
DOI: 10.1186/s12859-017-1495-1
|View full text |Cite
|
Sign up to set email alerts
|

Combining phylogenetic footprinting with motif models incorporating intra-motif dependencies

Abstract: BackgroundTranscriptional gene regulation is a fundamental process in nature, and the experimental and computational investigation of DNA binding motifs and their binding sites is a prerequisite for elucidating this process. Approaches for de-novo motif discovery can be subdivided in phylogenetic footprinting that takes into account phylogenetic dependencies in aligned sequences of more than one species and non-phylogenetic approaches based on sequences from only one species that typically take into account in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…As an outlook, the method proposed here is of a general significance, and it will be in the future also implemented in the more complicated case of direct target prediction for eukaryotic transcriptional regulators. Moreover, while the model was here applied in the context of PSWM, more complex models which take into account interdependences of nucleotides in TFBS were also developed ( Eggeling et al, 2015 ; Kulakovskiy et al, 2016 ; Nettling et al, 2017 ). While these methods lead to a better performance in some cases, more often (simpler) PSWMs perform better, which is likely due to overfitting, i.e., due to a limited number of TFBS from which the model is trained ( Benos et al, 2002 ; Nguyen and Androulakis, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…As an outlook, the method proposed here is of a general significance, and it will be in the future also implemented in the more complicated case of direct target prediction for eukaryotic transcriptional regulators. Moreover, while the model was here applied in the context of PSWM, more complex models which take into account interdependences of nucleotides in TFBS were also developed ( Eggeling et al, 2015 ; Kulakovskiy et al, 2016 ; Nettling et al, 2017 ). While these methods lead to a better performance in some cases, more often (simpler) PSWMs perform better, which is likely due to overfitting, i.e., due to a limited number of TFBS from which the model is trained ( Benos et al, 2002 ; Nguyen and Androulakis, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic footprinting improves the de-novo motif discovery by incorporating phylogenetic dependencies within the MSA in contrast to approaches based on sequences from only one species. Substitution models of DNA sequence evolution such as the F81 model ( Felsenstein, 1981 ) have been adapted to model the evolution of TFBSs in a position-specific manner, and it has been shown that these adapted models, which we call phylogenetic footprinting models (PFMs) for brevity, can detect TFBSs more accurately than models that neglect phylogenetic dependencies ( Clark et al , 2007 ; Gertz et al , 2006 ; Hardison and Taylor, 2012 ; Hawkins et al , 2009 ; Moses et al , 2004a ; Nettling et al , 2017 ).…”
Section: Introductionmentioning
confidence: 99%